2014
DOI: 10.5303/jkas.2014.47.4.123
|View full text |Cite
|
Sign up to set email alerts
|

A New Catalog of Silicate Carbon Stars

Abstract: A silicate carbon star is a carbon star which shows circumstellar silicate dust features. We collect a sample of 44 silicate carbon stars from the literature and investigate the validity of the classification. For some objects, it is uncertain whether the central star is a carbon star. We confirm that 29 objects are verified silicate carbon stars. We classify the confirmed objects into three subclasses based on the evolution phase of the central star. To investigate the effect of the chemical transition phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, this scenario could be unlikely for many objects because the timescale for such a transitional object to be observed as a silicate carbon star is predicted to be short (shorter than about 400 years; Kwon & Suh 2014). So far, about 29 silicate carbon stars have been identified in our Galaxy (Kwon & Suh 2014). Morris (1987) and Lloyd Evans (1990) suggested that a silicate carbon star is a binary system that has a primary carbon star and a low-luminosity companion.…”
mentioning
confidence: 99%
“…However, this scenario could be unlikely for many objects because the timescale for such a transitional object to be observed as a silicate carbon star is predicted to be short (shorter than about 400 years; Kwon & Suh 2014). So far, about 29 silicate carbon stars have been identified in our Galaxy (Kwon & Suh 2014). Morris (1987) and Lloyd Evans (1990) suggested that a silicate carbon star is a binary system that has a primary carbon star and a low-luminosity companion.…”
mentioning
confidence: 99%
“…We expect that most of them are likely to be binary systems rather than single stars (e.g., Kwon & Suh 2014). Silicate carbon stars could have a low-luminosity companion and a relatively long-lived disk of silicate dust that is supposed to be formed when the primary was still an O-rich AGB star.…”
Section: Binary Stars and Dusty Disksmentioning
confidence: 99%
“…Kwon & Suh (2012) presented a revised sample of 3373 O-rich AGB stars. Kwon & Suh (2014) presented a revised sample of silicate carbon stars (29 confirmed objects and 27 unconfirmed objects). Therefore, the updated catalog lists 3373 O-rich, 1168 C-rich, 362 Stype and 29 (+27) silicate carbon stars.…”
Section: A Catalog Of Agb Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon & Suh (2012) presented a revised list of 3373 O-rich AGB stars. Kwon & Suh (2014) presented a revised catalog of 29 silicate carbon stars, from which two of them are post-AGB stars.…”
Section: Previous Catalogs Of Agb Stars and Verificationmentioning
confidence: 99%